Hydrodynamics and heat transfer of laminar pulsating flow in a rectangular channel - Blythman, Richard (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2017)
The exploitation of flow pulsation is a potentially useful technique for enhanced cooling in single-phase cooling systems. This thesis contains parametric analyses of the hydrodynamics and heat transfer of a laminar hydrodynamically- and thermally-developed sinusoidally-pulsating flow in a rectangular channel using experimental measurements, novel analytical solutions and numerical CFD simulations. The pulsating velocity profiles over two bisecting planes of the channel cross-section are taken using particle image velocimetry (PIV). The pulsating wall temperature and convective heat flux profiles are measured using infrared thermography (IRT). To the best of the author’s knowledge, the velocity measurements constitute the first experimental verification of theory over two dimensions of a rectangular channel, while the local time-dependent temperature measurements are the first in a heated pipe or channel. It is found that the temperature profile is formed primarily by fluid displacement against the axial temperature gradient, although appreciable thermal diffusion occurs for low Prandtl numbers and long pulsation time scales. As a result, the local displacement gradient at the wall is approximately proportional to the local temperature gradient for the ideal constant temperature boundary condition. For realistic boundary conditions, the increased instantaneous near-wall velocity gradients of pulsating flow act to increase the heat flux at the wall. However, the velocity and temperature fields also interact through the non-obvious second order effect of oscillation-induced diffusivity that moves heat towards the channel entrance and reduces advective heat transfer with respect to steady flow. The time-averaged change in Nusselt number is universally negative, although intervals and local regions of heat transfer enhancement exist. The results are subject to the assumptions of a unidirectional, hydrodynamically- and thermally-developed flow with flow reversal precluded and negligible axial temperature gradient fluctuations, axial conduction and viscous heating.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin